MADRASAH DIMATA MASYARAKAT - Baso Marannu (EDUCANDUM, 2017)
The research conducted in Palu City is "Expectation of the Communitysending their children to The State Islamic School" using Mixed methods(Quantitative and Qualitative), by taking Participat Selection Model, thenumber of samples using tables Isaac and Michael with a 90% confidencelevel, the total student population MAN 1 and MAN 2 Kota Palu is 1,504students, for that sample taken by 230 parents of students or guardians ofstudents. The results of this study conclude in general expectations orexpectations of sending their children to school in the madrasah of the countryget a value of 3.00 ie the category is in accordance with some data support ie;(1) the educational value expected by the community toward madrasah gets2,90 (according category); (2) The public's expectation of madrasah moralityearns a score of 2.85 (appropriate category ); (3) the community's expectationof a future developed by madrasah gets 3.09 points (category Very suitable);(4) the community's expectation of scholarship applied in Madrasah is 3.02(very suitable category); (5) people's expectation on madrasah management is3.08 (very match category). This research recommends to the Ministry ofReligious Affairs as follows: First, the Ministry of Religious Affairs needs toinnovatively develop the managerial patterns of madrasah heads and theorganizational patterns of the Madrasah Committee